Intervención urbano - paisajística para la articulación del borde urbano deteriorado de la cabecera municipal de Candelaria con el río Párraga. (2024)
The development of architecture in the territories has transcended the mere conception of project elements and has become a crucial component in various social, cultural and economic spheres, especially in the context of urbanization. However, the accelerated urban expansion, motivated by population growth, has neglected the preservation of environmental resources, essential for human life.